Mitochondrial Reactive Oxygen Species Regulate Immune Responses of Macrophages to Aspergillus fumigatus - Hatinguais, Remi; Pradhan, Arnab; Brown, Gordon D.; Brown, Alistair J. P.; Warris, Adilia; Shekhova, Elena (Frontiers in Immunology, 2021)
Reactive Oxygen Species (ROS) are highly reactive molecules that can induce oxidative stress. For instance, the oxidative burst of immune cells is well known for its ability to inhibit the growth of invading pathogens. However, ROS also mediate redox signalling, which is important for the regulation of antimicrobial immunity. Here, we report a crucial role of mitochondrial ROS (mitoROS) in antifungal responses of macrophages. We show that mitoROS production rises in murine macrophages exposed to swollen conidia of the fungal pathogen Aspergillus fumigatus compared to untreated macrophages, or those treated with resting conidia. Furthermore, the exposure of macrophages to swollen conidia increases the activity of complex II of the respiratory chain and raises mitochondrial membrane potential. These alterations in mitochondria of infected macrophages suggest that mitoROS are produced via reverse electron transport (RET). Significantly, preventing mitoROS generation via RET by treatment with rotenone, or a suppressor of site IQ electron leak, S1QEL1.1, lowers the production of pro-inflammatory cytokines TNF-α and IL-1β in macrophages exposed to swollen conidia of A. fumigatus. Rotenone and S1QEL1.1 also reduces the fungicidal activity of macrophages against swollen conidia. Moreover, we have established that elevated recruitment of NADPH oxidase 2 (NOX2, also called gp91phox) to the phagosomal membrane occurs prior to the increase in mitoROS generation. Using macrophages from gp91phox-/- mice, we have further demonstrated that NOX2 is required to regulate cytokine secretion by RET-associated mitoROS in response to infection with swollen conidia. Taken together, these observations demonstrate the importance of RET-mediated mitoROS production in macrophages infected with A. fumigatus.